Acknowledging children's voice and participation in family courts: criteria that guide Western Australian court consultants - Banham, Vicki (2017)
The Australian family courts introduced Child Inclusive Conferencing after the country adopted the United Nations Convention on the Rights of the Child. The legislation governing these conferences is minimalistic but the Family Court Consultants in the Family Court of Australia and the Federal Circuit Court have well-developed and documented guidelines. The Family Court of Western Australia is, however, a separate entity and in the absence of regulatory guidelines its Family Consultants developed their own process and criteria. This model is unique, in Australia at least, because it has been organically developed by the practitioners providing the Child Inclusive Conferences with very little, if any, statutory and regulatory guidance. This model therefore serves as an example of how practitioners think child inclusive services should be offered.